Harnessing Nanoemulsion Technology for Enhanced Delivery of Canagliflozin in Type 2 Diabetes Therapy (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Canagliflozin, a selective sodium-glucose cotransporter-2 inhibitor indicated for the managementof type 2 diabetes mellitus (T2DM), is limited by poor aqueous solubility and suboptimal bioavailability, whichimpede its therapeutic potential. This study aimed to develop and comprehensively characterize a nanoemulsionbaseddelivery system to enhance the solubility, stability, and bioavailability of Canagliflozin. Preformulationanalyses confirmed the drug’s high solubility in methanol and DMSO, contrasted by poor water solubility andunsatisfactory micromeritic properties, indicating the necessity for formulation intervention. Materials andMethods: Nanoemulsions were prepared using appropriate oil, surfactant, and cosurfactant systems, and subjectedto sonication and high-pressure homogenization techniques to optimize droplet size and dispersion uniformity.Results and Discussion: Among the various formulations, F5 emerged as the most promising, exhibiting a dropletsize of 68.1 nm and superior homogeneity. Differential scanning calorimetry of F5 revealed a marked reduction inthe drug’s melting point, suggesting enhanced dispersion and possible conversion to an amorphous state. Fouriertransforminfrared spectroscopy indicated no significant chemical degradation, though minor spectral shiftssuggested non-covalent interactions between the drug and excipients. Collectively, the results support the successfuldevelopment of a stable nanoemulsion formulation capable of enhancing Canagliflozin’s physicochemical andbiopharmaceutical properties. Conclusion: This work underscores the potential of nanoemulsion technology as astrategic platform for improving the delivery of poorly soluble antidiabetic agents, thereby contributing to moreeffective and reliable therapeutic outcomes in the management of T2DM.